The Heterosexual Imaginary: Feminist Sociology and Theories of Gender - Ingraham, Chrys (Sociological Theory, 1994)
This essay argues that the material conditions of capitalist patriarchal societies are more integrally linked to institutionalized heterosexuality than they are to gender. Building on the critical strategies of early feminist sociology through the articulation of a materialist feminist theoretical framework, the author provides a critique of contemporary sex-gender theory. She argues that the heterosexual imaginary in feminist sociological theories of gender conceals the operation of heterosexuality in structuring gender and closes off any critical analysis of heterosexuality as an organizing institution.... every sociological concept and thesis, as well as the overall patterning of these concepts and theses, is potentially open for reconsideration... With the emergence of feminist sociological theory, the critical emphases in sociology are strengthened by an insistence that sociological work be critical and change-oriented... in an intensely reflexive way towards sociology itself (Lengermann and Niebrugge-Brantley 1990:318). We must produce a political transformation of the key concepts, that is of the concepts which are strategic for us (Wittig 1992:30).
Keywords: LGBTQIA2+; approches et analyses; capitalisme; cours; discipline; féminisme matérialiste; histoire et politique; hétérosexisme; hétérosexualité; patriarcat; premier cycle; sciences humaines; sexualité; soc2014; sociologie; systèmes d'oppressions; thématiques

Sodomites, invertis, homosexuels: perspectives historiques - Mendès-Leite, Rommel (Cahiers Gai-Kitsch-Camp, 1994)
Section: 193 pages : illustrations ; 21 cm
Keywords: 1900-1999; LGBTQIA2+; approches et analyses; cours; discipline; discours dominant; europe; france; histoire et politique; hétéronormativité; hétérosexisme; identités LGBTQIA2+; premier cycle; périodes historiques; queer; régions géographiques; sexualité; shm4000; systèmes d'oppressions; thématiques